Parent-Adolescent Conflicts Viewed from Emotional Independence and Parenting Styles - Vision, Vision; Savitri, Jane; Tjandraningtyas, Jacqueline (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2024)
The level of parent-adolescent conflicts increases after children attain puberty, facilitated by hormonal changes and cognitive development, which are believed to contribute to adolescents developing a sense of emotional autonomy from parents. These changes often lead to parent-adolescent conflicts, facilitating more mature and equal relationships between both parties. Parenting styles in responding to adolescents’ growing need for independence also influence the conflicts. Therefore, this study aimed to investigate the impact of adolescents’ emotional autonomy and parenting styles on the level of conflicts. To achieve this objective, a quantitative study was conducted on 386 Junior and Senior High School students from X Foundation, Denpasar. The results of multiple regression analysis showed that both emotional autonomy and parenting styles significantly impacted parent-adolescent conflicts. The contribution of these variables was more pronounced for mothers (50%) than fathers (43%). Both authoritative and authoritarian parenting styles were found to influence conflicts. Therefore, reducing parent-adolescent conflicts required considering adolescents’ emotional autonomy and fostering authoritative parenting styles.